Developing a recovery-focused therapy for older people with bipolar disorder: a qualitative focus group study. Issue 8 (4th August 2021) - Tyler, Elizabeth; Lobban, Fiona; Long, Rita; Jones, Steven H
Abstract : Objectives: As awareness of bipolar disorder (BD) increases and the world experiences a rapid ageing of the population, the number of people living with BD in later life is expected to rise substantially. There is no current evidence base for the effectiveness of psychological interventions for older adults with BD. This focus group study explored a number of topics to inform the development and delivery of a recovery-focused therapy (RfT) for older adults with BD. Design: A qualitative focus group study. Setting: Three focus groups were conducted at a university in the North West of England. Participants: Eight people took part in the focus groups; six older adults with BD, one carer and one friend. Results: Participant's responses clustered into six themes: (1) health-related and age-related changes in later life, (2) the experience of BD in later life, (3) managing and coping with BD in later life, (4) recovery in later life, (5) seeking helping in the future and (6) adapting RfT for older people. Conclusions: Participants reported a range of health-related and age-related changes and strategies to manage their BD. Participants held mixed views about using the term 'recovery' in later life. Participants were in agreement that certain adaptations were needed for delivering RfT for older adults, based on their experience of living with BD in later life. The data collected as part of the focus groups have led to a number of recommendations for delivering RfT for older adults with BD in a randomised controlled trial (Clinical Trial Registration: ISRCTN13875321 ).